2021
DOI: 10.3390/ijms22126194
|View full text |Cite
|
Sign up to set email alerts
|

Cumin Prevents 17β-Estradiol-Associated Breast Cancer in ACI Rats

Abstract: Breast cancer (BC) is a leading cause of cancer deaths in women in less developed countries and the second leading cause of cancer death in women in the U.S. In this study, we report the inhibition of E2-mediated mammary tumorigenesis by Cuminum cyminum (cumin) administered via the diet as cumin powder, as well as dried ethanolic extract. Groups of female ACI rats were given either an AIN-93M diet or a diet supplemented with cumin powder (5% and 7.5%, w/w) or dried ethanolic cumin extract (1%, w/w), and then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Furthermore, the major phytochemical constituents of cumin are cuminaldehyde and cymene, which have been proven to stimulate the activities of cytochrome p450s, aryl hydroxylase, and N-demethylase in rats [ 114 ]. The cumin powder diet reversed the expression levels of miR-206 that were highly modulated by 17ß-estradiol (E2) treatment in August Copenhagen Irish (ACI) rats with breast cancer [ 115 ].…”
Section: The Biological Function Of Mir-206mentioning
confidence: 99%
“…Furthermore, the major phytochemical constituents of cumin are cuminaldehyde and cymene, which have been proven to stimulate the activities of cytochrome p450s, aryl hydroxylase, and N-demethylase in rats [ 114 ]. The cumin powder diet reversed the expression levels of miR-206 that were highly modulated by 17ß-estradiol (E2) treatment in August Copenhagen Irish (ACI) rats with breast cancer [ 115 ].…”
Section: The Biological Function Of Mir-206mentioning
confidence: 99%
“…The excretion of fecal bile acids and neutral sterols benefi cially increased, and cumin showed nourish the colon and reduced the activity of mucinase enzymes and β-glucuronidase [56]. β-glucuronidase rise hydrolysis of glucuronide compound and liberate toxin whereas the rise in mucinase activity may enhance the hydrolysis of the colon's protecting mucins [57]. Histopathology analysis revealed that decreased infi ltration into the submucosa, lesser papillae, and fewer changes in the cytoplasma cell in the cumin treated colon [46].…”
Section: Anti-cancer Effectsmentioning
confidence: 99%